Prequal: Analyzing The Forming Factors Of Telkomsel's Prepaid Customer Service Quality In Bandung - Irena Larashati; Ashila Dwiyanisa; Imelda Megawati (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
The development of communication technology has pushed fierce competition between each telecommunications service provider company in Indonesia. Therefore every company needs to understand services that can satisfy consumers to maintain it so that it does not move to compete for products. This research conducted to validate the scale of service quality measurement that can satisfy Telkomsel pre-consumer consumers in the city of Bandung. The study conducted using the EFA method with the Principle Axis Factoring (PAF) technique. Testing in this study conducted using Telkomsel prepaid consumers in Bandung as many as 237 respondents. The results showed that eight factors formed service quality, namely empathy, facilities, customer reliability and independence, employee attractiveness and facilities, employee competence, assurance, communication skills, and information quality. These factors are called prequal, which is the development of a validated instrument.